An inside look into a problem of innovation in selected Priority Axis of Innovative Economy Operational Programme 2007 - 2013 for Lower Silesia Region - Marta Zaleska; Zbigniew Mogiła; Joanna Knap (European Regional Science Association (ERSA), 2014)
The economic crisis and the declining competitiveness of Europe, led to the orientation of cohesion policy for smart growth based on knowledge and innovation. Poland and its regions are in a specific socio-economical position characterized by a low share of higher value-added products and high technology-intensive ones in total export. They still need to bridge the gap towards the more developed EU countries and regions by shaping their competitive advantage. The only way to develop and maintain a competitive advantage is to trigger knowledge- and innovation-based entrepreneurship. Cohesion policy funds open up great opportunities for innovation. Nowadays, when the programming period 2007 - 2013 came to an end, it is increasingly important to assess effectiveness of the EU intervention in the context of innovation. The main aim of this study is to present the methodology that allows to assess the role of the EU operational programs in determining the long-term development based on pro-innovative business sector. To present methodology clearly, it will be presented on the example of the Innovative Economy Operational Programme 2007 - 2013 (IE OP) for Lower Silesia region. The first stage of the study will contain a review of literature and a proposition of typology of innovations in the context of their impact on the long-term development. The detailed analysis of more than 100 projects under the IE OP in Lower Silesia will be done to assess effectiveness of the implementation of co-financed research & development projects. The aim of this stage is to deepen the knowledge about the positive and negative factors affecting the implementation of the results of R&D in practice. On the base of the typology and results from previous stages, projects will be classified to created categories of innovation (e.g. imitative, product-oriented, process-oriented etc.). The results will verify whether in the analyzed projects dominates imitative type of innovation, which is typical of regions that are still shortening the distance towards the centers of socio-economic development. This, however, can lead to an "average income trap" that does not guarantee non-cost competitiveness. The results of the study may be used in future analysis as a contribution to the macroeconomic quantitative studies of the cohesion policy impact.
Keywords: 330; regional development; innovation; cohesion policy